Therapeutic effects of Kangxian Yanshen formula on patients with chronic kidney disease stages 3–4: a retrospective cohort study - Chu, Aojiao; Wei, Wenqian; Liu, Ni; Zhang, Fan; Zhang, Xianwen; Li, Xueling; Zheng, Rong; Ma, Zhifang; Li, Yi; Rong, Shu; Zhong, Yifei (Frontiers in Medicine, 2024)
Background: This study retrospectively evaluated the actual efficacy of Kangxian Yanshen Formula Chinese medicine on renal function-related indicators in chronic kidney disease (CKD) stage 3-4 patients.In this retrospective cohort study, we collected 212 adult CKD patients with baseline estimated glomerular filtration rate (eGFR) of 15-60 ml/min/1.73 m 2 .All participants received usual care (i.e., Western medications), and participants in the exposure group (n=109) were additionally prescribed Kangxian Yanshen Formula Chinese medicine. The primary outcome was an adjusted hazard risk and 95% confidence interval (95% CI) of a 30% decrease in eGFR at month 36 from baseline.In terms of eGFR, among participants treated with additional Kangxian Yanshen Formula, after adjusting for covariates, there was a 57.1% reduction in the risk of a 30% decline from baseline in eGFR among participants in the Kangxian Yanshen Formula group compared with the Western medicine group (adjusted hazard risk: 0.429; 95% CI 0.269-0.682). In addition, participants in the Kangxian Yanshen Formula group had a significantly higher change in eGFR from baseline to month 12 than those in the western medicine group (3.40±11.62 versus -3.87±8.39; between-group difference Δ5.61 [±2.26 standard deviation] mL/min/1.73 m 2 ; P=0.014). Participants in both groups showed a decreasing trend in eGFR at months 24 and 36.In patients with stage 3-4 CKD, Kangxian Yanshen Formula Chinese medicine therapy may help delay eGFR decline, but high-quality randomized controlled trials are needed to validate the results further.